Case report: Renal adenoma in a captive ocelot (Leopardus pardalis) in Costa Rica - Romero-Vega, L. Mario; Medlin, Sam; Hagnauer, Isabel; Alfaro-Alarcón, Alejandro; Williams, Bruce (Frontiers in Veterinary Science, 2024)
Reports of renal neoplasia are rare in neotropical wildcats. Ocelots (Leopardus pardalis) are mediumsized wildcats living in America's tropical forests. A 12-year-old captive Ocelot was diagnosed with a renal mass occupying approximately 25% of the total right kidney volume. The tissue was stained with routine Hematoxylin and Eosin (H&E) and Periodic Acid-Schiff (PAS). Immunohistochemistry with the following markers was performed: Cytokeratin (CK) AE1/AE3, CK19, CK 7, CD10, Vimentin, Melan A, HMB45, Pax-8, and Wilm's Tumor 1 (WT1). Histopathology revealed a well-differentiated epithelial tubular neoplasia with less than one mitotic figure per 2,37mm 2 field. Vimentin and Pax-8 were the only positive markers. Immunohistochemically, the neoplasia was diagnosed as a renal adenoma. Renal adenomas are seldom reported in neotropical wildcats. Reports on wild species are valuable for properly establishing a clinical prognosis in captive species. To the best of the authors' knowledge, this is the first report that provides detailed microscopic and immunohistochemical descriptions of renal adenoma in a captive ocelot.